Effect of Maca (Lepidium meyenii) powder dietary supplementation on performance, egg quality, yolk cholesterol, serum parameters and antioxidant status of laying hens in the post-peak period - OMURTAG KORKMAZ, BURCU İREM (EUGEN ULMER GMBH CO, 2016)
The present study investigated the effects of dietary supplementation with Maca powder on the performance, egg quality, serum parameters, hormones and antioxidant enzyme levels of laying hens in their post-peak period. A total of 150 hens, 56 week of age, were separated into three treatment groups (50 hens per group). Over 16 weeks, diets were supplemented with Maca powder at concentrations of 0 (control), 5 and 10 g/kg respectively. Performance and egg quality were not significantly influenced by the supplementation of Maca powder. Cholesterol contents of the yolk were not influenced by the experimental diets. At the end of the study, no significant difference in the levels of serum glucose, total triglyceride and total cholesterol, calcium, phosphorus, progesterone and oestradiol was detected. However, serum magnesium levels decreased as the rate of Maca powder increased (P< 0.05). A significant increase in serum glutathione peroxidase (GPx) was measured in the hens fed with 10 g/kg Maca powder. In conclusion, Maca powder had neither positive nor adverse impacts on performance, egg quality, yolk cholesterol content, serum parameters (except magnesium) and hormones. Despite that serum magnesium levels were adversely affected, Maca powder may enhance the antioxidant status, specifically GPx, of laying hens in the post-peak period.
Keywords: Laying hen; nutrition; Maca; Lepidium meyenii; egg quality; antioxidative status; METABOLISM; EXTRACT; RATS; OSTEOPOROSIS; EFFICIENCY; JUVENILES; HORMONE; GROWTH